An Overview of GIS Used in Oil Palm Plantation - Zamri, Siti Hajar; Mohamad Abdullah, Nazirah (Recent Trends in Civil Engineering and Built Environment, 2022)
Oil palm plantations have expanded rapidly in recent decades, especially in major oil palm producing countries like Malaysia and Indonesia. The rapid development of the information technology and computers are affecting the way people perceive the overall plantation technology. Oil palm plantation mapping and monitoring needed more precise technological innovation. Previous studies have proven the capability of Geographical Information Systems (GIS) collecting information and interpreting data for mapping oil palm plantations. Therefore, this research study conducted to evaluate the accuracy of technology in term of data processing and its effectiveness for oil palm plantation mapping using GIS approach. This study will be conducted by systematic literature review. As result from research papers that been selected shown that this technology had high accuracy value which is 86.0% in producing mapping of oil palm plantations as well as assist in plantation management.